Bending technology of high strength steel sheets and tools for its realization - V. A. Tаmilа; M. L. Nesterovich (Литьë и металлургия)
The article proposes and theoretically justifies a method for bending high-strength steels with compression. The technology allows to get parts from high-strength steels without cracks along the bending line. In the case of bending according to the proposed method, the deformation is carried out by the combined action of longitudinal and lateral forces. Equitations are derived showing the stress distribution over the cross section in the deformation zone. The article proposes and theoretically justifies a method for bending high-strength steels with compression. The technology allows you to get parts from high-strength steels without cracks along the bending line. In the case of bending according to the proposed method, the deformation is carried out by the action of longitudinal and transverse forces. Equitations were derived for finding the longitudinal compressive force at which the neutral layer in the workpiece moves to the outer surface based on the equations of stress distribution. Equitations are derived for finding the moment created by the longitudinal compressive force, as well as the moment formed by the action of compressive stresses, which made it possible to derive the equation for the external bending moment during bending with compression. Equitation is derived for finding the shoulder of the force action creating an external bending moment. Equitation is derived for finding the force of the punch for bending with compression.